Cationic Rhodium(I)‐Catalyzed Carbonylative [2+2+1] Cycloaddition of Diynes. Issue 11 (7th October 2020) - Morimoto, Tsumoru; Jia, JingWen; Yamaguchi, Yoshiko; Tanimoto, Hiroki; Kakiuchi, Kiyomi
Abstract: We describe Rh(I)‐catalyzed carbonylative [2+2+1] cycloaddition reactions of diynes with CO to give cyclopentadienone derivatives (CPDs). Previous reports on the use of neutral rhodium(I) complexes, such as [RhCl(cod)]2 and RhCl(PPh3 )3, indicate that no CPD products are formed or that they are produced in low yields, even at elevated temperatures. The reaction described herein, which uses a cationic rhodium(I) complex, [Rh(cod)2 ]BF4, as a catalyst, proceeds smoothly at room temperature to give cyclopentadienone derivatives. The key to this is the use the cationic rhodium(I) complex as a catalyst, which produces an additional coordination site on the rhodium for the substrate (a diyne) to approach, than neutral rhodium complexes. Abstract : A cationic rhodium(I) complex, [Rh(cod)2 ]BF4, catalyzes carbonylative [2+2+1] cycloaddition reactions of diynes with CO at room temperature to give cyclopentadienone derivatives.